Physicianpatient communication : a tool for optimum satisfaction - Talukder, Abu Mohammad; Mahejabin, Farzana; Faruk, Abdullah Al; Sultan, Quazi Rakibus; Sufian, Abu; Mannan, Md Abdul (Northern International Medical College Journal, 2015)
Abstract not available Northern International Medical College Journal Vol.6(2) 2015: 48-49